Combining TMD and TLCD: analytical and experimental studies. Issue 167 (August 2017) - Di Matteo, A.; Pirrotta, A.; Tumminelli, S.
Abstract: In these years several research efforts have been focused on developing efficient and reliable control devices for mitigating the structural response of tall and lightly damped buildings in case of strong dynamic excitations, such as wind and earthquake ones. In this context, Tuned Mass Dampers (TMDs) represent probably the most common control device due to their high control performances. On the other hand, Tuned Liquid Column Dampers (TLCDs) are increasingly becoming more popular because of some of their attractive features, cost-effectiveness among the others, even though they yield slightly less control performance compared to the classical TMDs. Aiming at combining the beneficial effects of the TMD and the attractive characteristics of the TLCD, in this paper a novel control device is introduced which is realized joining this two systems. The pertinent equations of motion are derived, and the analytical study is developed to analyze the control performance of this device. Finally, theoretical results are validated via vast experimental campaign undertaken in the Laboratory of Experimental Dynamics of the University of Palermo, Italy.